MathOverflow is a question and answer site for professional mathematicians. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Let $$G=\langle x, y, z\mid xyx^{-1}=zy, xzx^{-1}=z, yz=zy\rangle,$$ denote $l^1(G)^{\times}$ to be the set of units in $l^1(G)$, which we have considered as a ring with multiplication defined by the usual convolution, i.e., $(\sum_{g\in G}\lambda_gg)(\sum_{h\in G}\mu_hh)=\sum_{g, h\in G}\lambda_g\mu_hgh$.

Can we find $l=p_1(y, z)x^{n_1}+\cdots+ p_k(y,z)x^{n_k}\in l^1(G)^{\times}$ such that $$\sum_{i=1}^k2^{n_i}p_i(y,z)(1-z^{n_i}y)=0\;?$$

Here, $\forall~ 1\leq i\leq k, ~p_i(y,z)\in \mathbb{Z}G$ and $n_1<\cdots<n_k\in\mathbb{Z}$ to be determined. Note that the group element $x$ does not appear in $p_i(y, z)$.


1, This problem was asked previously in MSE, but no answer appeared, so I think it might be suitable for MO.

2, This problem is related to a modified Ore condition. I want to show that $l$ does not exist, suppose it exists, then I have considered the natural quotient map $\phi: G\to H=G/\langle z^2\rangle$. Note that it would induce a map $\phi: l^1(G)^{\times}\to l^1(H)^{\times}$, then $\phi(l)\in l^1(H)^{\times}$, but I still could not handle this..

share|cite|improve this question
why some symbols could not appear? Anyone helps fix this? – Jiang May 30 '13 at 7:38
@Jiang: I've edited the MathJax code. There are some issues with how it works here, but they should go away when MathOverflow moves to the SE 2.0 network sometime soon: – Zev Chonoles May 30 '13 at 8:00
@Zev Chonoles, thanks! – Jiang May 30 '13 at 8:40
How about $l = 2(1-zy) - (1-y)x$? – user91132 Jun 4 '13 at 8:39
@Konstantin, thanks for your comment. For this $l$, we can check that $l^{-1}=sum_{n\geq 0}\frac{1}{2^{n+1}}(1-y)(1-z^ny)^{-1}(1-z^{n+1}y)^{-1}x^n\not\in l^1(G)^{\times}$ – Jiang Jun 16 '13 at 9:53
up vote 1 down vote accepted

Omit this problem, we can take $l=z+\frac{1}{2}(-z-1)x+\frac{1}{4}x^2$, then $l^{-1}=\sum_{n\geq 0, m\geq 0}\frac{1}{2^{n+m}}x^{n+m}z^{-m-1}\in l^1(G)$.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.